Optimization of Village Office Services through Service Standards, Complaint Services, and Community Satisfaction Surveys - Mathory, Eljihad Akbari Syukriah; Ramdhani, Arindah Mutiara; Reston, Rhegyna Vanessa; Nurjannah, Miftahul (Universitas Lambung Mangkurat, 2025)
This community service aims to improve the quality of public services in Coppo Tompong Village, Mandalle District, Pangkajene and Islands Regency, with a focus on complaints, community satisfaction surveys, and service standards. The method used in this community service uses the PAR method. In the PAR method, the community becomes a collaborative partner, not an object of research. The PAR method has several principles, including the principles of participation, action orientation, triangulation, and flexibility. The results of initial observations showed several problems, including complaints services that were still manual, the absence of service standards, and no forum for assessing community satisfaction. The solutions carried out were the creation of a Google Form-based complaint service, the preparation of service standard documents, and the creation of a community satisfaction survey. The community satisfaction survey conducted aims to measure how satisfied the community is with the services received, with the survey results showing that services at the Coppo Tompong Village Office fall into the